At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Ask your questions and receive precise answers from experienced professionals across different disciplines. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

Solve the system of equations by substitution.

y = 4x -1

2x + 2y = 3


Sagot :

Answer:

(0.5, 1 )

Step-by-step explanation:

y = 4x - 1 → (1)

2x + 2y = 3 → (2)

Substitute y = 4x - 1 into (2)

2x + 2(4x - 1) = 3 ← distribute parenthesis and simplify left side

2x + 8x - 2 = 3

10x - 2 = 3 ( add 2 to both sides )

10x = 5 ( divide both sides by 10 )

x = [tex]\frac{5}{10}[/tex] = 0.5

Substitute x = 0.5 into (1)

y = 4(0.5) - 1 = 2 - 1 = 1

solution is (0.5, 1 )